Closing the implementation and coordination gaps in agroecological policies in Zimbabwe: A bibliographic survey on global lessons - Marenya, Paswel P.; Ngoma, Hambulo; Matangi, Dorcas; Chimonyo, Vimbayi G. P.; Chiduwa, Mazvita S. (CGIAR, 2023)
The thirteen principles of agroecology span the scientific, social policy and institutional landscape. The slow progress towards AEI can be traced in many cases, not to lack of policies, but effective coordination and implementation gaps. In this six-part bibliographic survey, we review the global landscape on policy coordination issues and related policy theories of change, institutions for agroecology, elements of food systems transformation, agroecological transitions, farming innovations for agroecologically sensitive production, and finally some examples from Africa. The review brings forward at least two critical gaps in the policy intention-implementation gap. The need for overarching agroecological policy theories of change to help coordinate individual policies as well as achieve inter-sectoral coordination.